Madri di Einar Schleef - Dreysse, Miriam (Kritik. Rivista di letteratura e critica culturale, 2024)
Mütter is a very controversial play; spectators leave the theater in droves, aggressively worded critiques pour in from the newspapers. The reason for the violence of the reactions is primarily the chorus, which is in fact the undisputed star of the play, not only because of its constant presence on stage and the quantity of choruses, but also because of the specific way in which it is understood and used. Schleef always stages the chorus as an autonomous formal element, as an enclosed unit in itself, which is clearly detached as much from the actors and actresses as from the audience, asserting itself in its own distinct independence.